Recent Publications (Quarterly Journal of Economics, 1967)
Recent Publications Get access The Quarterly Journal of Economics, Volume 81, Issue 3, August 1967, Pages 536–544, https://doi.org/10.1093/qje/81.3.536 Published: 01 August 1967